The anticancer activity of dichloromethane crude extract obtained from Calea pinnatifida - Foglio MA; Figueira GM; Tinti SV; Sousa IM; Santos AN; Silva KA; Marchetti GM; Carvalho JE (Dove Medical Press, 2012)
Gabriela M Marchetti,1,2 Karina A Silva,3 Arianny N Santos,3 Ilza MO Sousa,3 Sirlene V Tinti,2 Glyn M Figueira,4 Mary A Foglio,1,3 João E Carvalho1,21Programa de Pós Graduação em Biologia Celular e Estrutural, Institute of Biology, 2Pharmacology and Toxicology Department, Multidisciplinary Center for Chemical, Biological and Agricultural Research (CPQBA), 3Phytochemistry Department, CPQBA, 4Agrotechnology Department, CPQBA, University of Campinas – UNICAMP, Campinas, BrazilAbstract: The genus Calea is reported for many biological activities such as antiinflammatory, antiplasmodial, antifungal, antimicrobial, and cytotoxic activities. Most of the pharmacological activities are credited to germacranolides, a sesquiterpene lactone common to this genus. Dried aerial parts of Calea pinnatifida Banks were extracted with dichloromethane, which generated the dichloromethane crude extract (DCE). The main purpose of this study was to evaluate the anticancer activity of DCE performed in sulforhodamine B cytotoxicity in vitro assay against human cancer cell lines and in vivo Ehrlich models. The DCE showed a high potency and selectivity for the melanoma and kidney cell line. Two in vivo assays were also conducted in the Ehrlich ascites tumor and Ehrlich solid tumor. In the Ehrlich ascites tumor assay, the treatment with DCE increased survival rates at the highest dose (200 mg/kg). Interestingly, in the Ehrlich solid tumor, by increasing the number of treatments from one to three times a week, the tumor growth was inhibited by a lower dose (100 mg/kg). These results encouraged follow-up studies with C. pinnatifida in order to identify the active principles and to determine the anticancer mechanism of action.Keywords: Calea pinnatifida, cytotoxicity, cancer, Ehrlich ascitic tumor, Ehrlich solid tumor